Community Participation Analysis in Preparation of Regional Development Work Plans in Pasangkayu Regency - Syahril; Hazairin Zubair; Lukman Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This research aims to provide a comprehensive description of Community Participation in the Formulation of Regional Development Work Plans in Pasangkayu District. The study's findings indicate that community involvement in every stage of development planning has not been fully realized, attributable to various factors such as budget constraints and government policies, both at the executive and legislative levels. The research adopts a descriptive approach with a qualitative methodology. Data sources include interviews with informants and document analysis. The data analysis method utilizes the interactive qualitative data analysis model proposed by Miles, Huberman, and Saldana (2014), involving data collection, data condensation, data presentation, and drawing conclusions. This approach sheds light on the complexities surrounding community participation in the development planning process and underscores the impact of budgetary limitations and governmental policies on the extent of community involvement in the decision-making processes.